Kritik Sosial Generasi Z dalam Konten TikTok Pray For Sumatra: Analisis Narasi Bencana dan Kepemimpinan: Analisis Narasi Bencana dan Kepemimpinan - Cecep Ahmad Topa (HK Publishing, 2026)
Abstract This study analyzes how Generation Z uses TikTok to create critical narratives about the November 2025 flood disaster in Sumatra and respond to government leadership, rather than simply expressing sympathy. Using a qualitative approach with a focus on narrative analysis, this study explores five TikTok videos using the hashtag #PrayForSumatra created by young content creators aged 17 to 25. The results of this study show that the content is not only about prayer and loss, but also contains social criticism organized in six recurring narrative patterns. These findings confirm that Generation Z is not only a passive and empathetic audience, but also an active communicator, utilizing digital media to change the way society understands the disaster, from a mere